Analisis Deskriptif Dampak Pendidikan Barak Militer terhadap Pola Asuh Anak Usia Dini dalam Perspektif Islamic Mindful Parenting - Rahmah, Maisya Febriani; Riyadi, Hendar; Faatinisa, Esty; Nurjanah, Pitri; Abidin, Fajar; Kamila, Nisrina Cahya (Yayasan Cendekia Gagayunan Indonesia, 2025)
The phenomenon of military barracks education, initiated by West Java Governor Dedi Mulyadi in May 2025, has sparked controversy. This is primarily due to its involvement in coaching students with deviant behavior, including gadget use. Public discourse has emerged regarding the effectiveness of this military barracks education model as a response to a perceived discipline crisis, which emphasizes children's obedience to parents through a rigid system. This study aims to investigate whether the military barracks education approach aligns with the principles of Islamic Mindful Parenting. Islamic Mindful Parenting is a synthesis of Islamic parenting principles with mindfulness, designed to foster internal self-control in children. The research employs a quantitative approach with descriptive methods for data collection and analysis. Data was gathered through questionnaires completed by parents.The results indicate that most parents favored the educational content of military barracks and were interested in this approach. However, the explanations provided by parents contradicted the principles of Islamic Mindful Parenting. The rigid military approach can cause stress and insecurity in children, and hinder communication and the development of critical thinking. This contrasts with Islamic Mindful Parenting, which emphasizes empathy, compassion, and the development of character from within, by focusing on attentive listening, non-judgmental acceptance of self and child, awareness of one's own and the child's emotions, self-regulation in the parenting relationship, and a compassionate attitude towards oneself and the child.